Brain-imaging studies of treatment-resistant schizophrenia: a systematic review. (May 2016) - Mouchlianitis, Elias; McCutcheon, Robert; Howes, Oliver D
Summary: Around 30% of patients with schizophrenia show an inadequate response to antipsychotics—ie, treatment resistance. Neuroimaging studies can help to uncover the underlying neurobiological reasons for such resistance and identify these patients earlier. Additionally, studies examining the effect of clozapine on the brain can help to identify aspects of clozapine that make it uniquely effective in patients with treatment resistance. We did a systematic search of PubMed between Jan 1, 1980, and April 13, 2015, to identify all neuroimaging studies that examined treatment-resistant patients or longitudinally assessed the effects of clozapine treatment. We identified 330 articles, of which 61 met the inclusion criteria. Replicated differences between treatment-resistant and treatment-responsive patients include reductions in grey matter and perfusion of frontotemporal regions, and increases in white matter and basal ganglia perfusion, with effect sizes ranging from 0·4 to greater than 1. Clozapine treatment led to reductions in caudate nucleus volume in three separate studies. The available evidence supports the hypothesis that some of the neurobiological changes seen in treatment-resistant schizophrenia lie along a continuum with treatment-responsive schizophrenia, whereas other differences are categorical in nature and have potential to be used as biomarkers. However, further replication is needed, and for neuroimaging findings to be clinically translatable, future studies need to focus on a-priori hypotheses and be adequately powered.